Implikasi Yuridis Hilangnya Keanekaragaman Hayati Terhadap Sistem Ekologi - Bandus Tira Wijaya; Muhammad Hisyam Rasyidi; I Made Griya Astaman; Sesar Sumarno (INDO PUBLISHING, 2026)
Biodiversity loss is a global environmental issue that significantly impacts the stability of ecological systems and creates legal implications within national and international environmental law frameworks. This phenomenon is triggered by anthropogenic activities such as deforestation, overexploitation of natural resources, pollution, and climate change, which accelerate ecosystem degradation. This study aims to analyze: (1) the legal implications of biodiversity loss on ecological systems, and (2) the effectiveness of legal regulations in protecting biodiversity. The method used is normative legal research with a legislative and conceptual approach. The results of the study indicate that biodiversity loss not only impacts ecosystem imbalance but also gives rise to the state's legal responsibility to ensure environmental protection through national legal instruments such as the Environmental Protection and Management Law and international commitments such as the Convention on Biological Diversity. However, the implementation of these regulations still faces obstacles in terms of law enforcement, institutional coordination, and effective oversight. In conclusion, strengthening more responsive and integrative legal instruments is needed to ensure sustainable biodiversity protection and maintain the stability of ecological systems.